The Legal Appraisal of the Nature of Liability of Land Transport Operators in Cases of Accidents in Cameroon - Kombo, Kutiefe Umaro (International Multilingual Journal of Science and Technology, 2026)
Land transport operators in Cameroon can be criminally and civilly liable as a result of an accident resulting from their actions. This is provided for in section 289(1) of the penal code1. The criminal liability can be either in tort law, like in negligence, vicarious liability and strict liability, as well as under contract law. The criminal liability can be for an imprisonment term, the payment of a fine, or loss of life or destruction of property. However, the nature of liability in cases of accidents is faced with problems in Cameroon, as the cases suffer from continuous delay before the courts, weak sanctions provided in the penal code and more. This paper sets out to examine the efficiency of the nature of liability of transport operators in cases of accidents in Cameroon. A doctrinal research method has been adopted where the researcher has analyzed both primary and secondary sources of information. The primary sources are the laws and cases decided by courts, while the secondary sources are other write up which the researcher consulted to complete the research paper. Our findings reveal that the laxity of the courts and weak sanctions provided by the Penal code affects the effectiveness of the liability regime for transport operators in cases of accidents. We recommend that the penal code be revised and a more stringent criminal sanction be put in place. Also, a separate court system should be set up for disputes related to accidents to solve the problem of continuous delay before the courts.
Keywords: Accidents; Land Transport Operators; Nature of Liability; Responsabilité; Transport par route; Transporteur

The Effectiveness of the Legal Frameworks in the establishment of Liability of Land Transport Operators in cases of Accidents in Cameroon: A Critical Appraisal - Kombo, Kutiefe Umaro (International Multilingual Journal of Science and Technology, 2025)
The liability of land transport operators in Cameroon is guaranteed by a good number of laws including; the constitution of Cameroon, the penal code, the 2001 law governing the Profession of Road Transport Operators, the 2023 law governing the rail sector in Cameroon and more. Such liability can be under the Tort of negligence, vicarious liability, or strict liability as provided for under section 289(1) of the Cameroonian penal code on Unintentional killing. However, the laxity of the courts in handling accident-related disputes, the contradictory and vague nature of the laws on the liability regime and even the lenient nature of the sanctions provided for by these laws do not meet up with the rate of accidents today in Cameroon. This article therefore has as its objective to examine the effectiveness of the legal frameworks in the establishment of liability of land transport operators in cases of accidents in Cameroon. Arguably, the author holds that the legal frameworks establishing the liability of land transport operators in cases of an accident in Cameroon are ineffective. A doctrinal research method has been adopted where both primary and secondary sources of information have been consulted. Our finding reveals that; the ineffectiveness of legal frameworks in the establishment of the liability of land transport operators in cases of accidents is a result of the laxity of the courts in implementing the laws and, the vague and contradictor nature of the law. We, therefore, recommend that; separate court hearings should be set for accident-related disputes and judges trained only on that, the laws should be revised, the sanctions in cases of accidents should be increased and all mitigating circumstances in cases of accidents should not be taken into consideration like a first-time offender, the plea of guilt etc.
Keywords: Accidents; Cameroun; Land Transport Operators; Liability; Opérateurs de transport terrestre; Responsabilité; Transport terrestre

The Rotterdam Rules Convention: United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea 2008 - Laurijssen, Peter (CMI, 2024)
Keywords: MARITIME LAW; UN Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (2008)

Chapter 11, First principles in transportation law and policy - Levine, Jonathan; Shill, Gregory H. (A Research Agenda for US Land Use and Planning Law, 2023)
The main purpose of transportation is connecting people to destinations they value. This seemingly banal statement would, if taken seriously in policymaking, upend transportation and land use planning. Today, planning agencies rely on key performance indicators (KPIs) to measure outcomes. While ostensibly neutral and technical, these measurements in fact imply policy judgments and drive legal consequences. They operate both as a shield against litigation and as a sword to justify new projects. But the way KPIs are set up reflects confusion about basic purposes. They are used to plan and evaluate based not on the ability to reach anything but rather simply to accelerate the speed of traveling. We seek to anchor transportation policy discussion in first principles. The shift we propose is mode agnostic in that it is relevant to all means of transportation. Even so, shifting from a goal of speed to one of reachability would be a leap. We believe such a shift suggests important open questions regarding the barriers to reform and we engage a few of them.

Legal scope of the carrier's liability in the contract of carriage of goods by sea - Drici, Amina (Journal OF LEGAL STUDIES, 2023)
The area of responsibility of the sea freight carrier is to determine the scope of liability over time for damage to the goods and is reflected in the search for the beginning and end of its liability; as well as the determination of the damage which triggers the carrier's obligation to compensate for the losses, damage, delay and determine the persons responsible for the damages for which the recipient or beneficiary of the goods has the right to recourse.
Keywords: Liability; Material scope; Personal scope; Sea carrier; Time scope; Transportation of goods

Determining the Liability for Carriage of Goods by Road in West Africa - Can OHADA Uniform Rules on Transport be a Foundation? - Osinuga, Damilola (Southern African Journal of Policy and Development, 2022)

The legal framework for multimodal transport in West Africa: the African Continental Free Trade Area in perspective - Osinuga, Damilola (World Maritime University, 2022)
This thesis examines how multimodal transport can play a role in achieving the objectives of the African Continental Free Trade Area (AfCFTA). The thesis argues that multimodal transport is cheaper compared with unimodal transportation. While there are a number of issues affecting the operationalisation of multimodal transport in Africa, this study considers, at its core, the legal regimes and other fragmented institutional and governance frameworks of multimodal transport in West Africa. The fragmentation of the legal framework governing multimodal transport leads to uncertainty and unforeseeability of the liability of parties involved in multimodal transport, consequently leading to increased legal costs. There is an undisputed view that for effective regional integration, which Africa is seeking to achieve through the establishment of the African Continental Free Trade Area, there is a need to eliminate all trade barriers. Trade barriers (tariff or non-tariff barriers) should be removed to improve competitiveness and reduce trade friction costs. In other words, to achieve the objectives of the African Continental Free Trade Area, it is essential that all unnecessary costs associated with trade are eliminated or reduced to the barest minimum. The process of doing this is called trade facilitation. This thesis looks at the impact of trade facilitation on regional integration and trade. This thesis’ original contribution to knowledge is that Africa’s regional integration process needs cost-effective transportation in order to achieve smooth market access, and multimodal transportation can provide the most cost-effective solution. However, the legal uncertainty and complexities that could potentially ensue from the use of multimodal transport make it unattractive to prospective users. Accordingly, actions must be taken to reduce legal ambiguity and create a system in which liability is foreseeable and predictable. This study reveals that the current legal framework is incomplete, unsatisfactory and, ultimately, leads to uncertainty. The thesis further contends that neither the option of freedom of contract nor improving the current system of various Economic Community of West African States (ECOWAS )member-states’ view of multimodal transport, can significantly improve the current fragmented system or deliver the needed certainty. Accordingly, the thesis proposes that a modified uniform system would help achieve the legal certainty needed for multimodal transport. The thesis finally submits that the ECOWAS should establish a legally binding, regional governance regime on multimodal transport and a majority of its member-states should ratify the instrument.

The impact of the pandemic on the legal regulation of entrepreneurial activity of transport companies - Rubtsova, Natalya (Transportation Research Procedia, 2022)
The purpose of this paper is to analyze the trends of legal regulation in the business activity under the conditions of new coronavirus infection. The dialectical method of research in conjunction with a retrospective and comparative analysis made it possible to identify three main trends in the legal regulation of entrepreneurial activity in the framework of new socio-economic realities. The increasing role of state regulation of entrepreneurial activity, based on the use of public and legal means, due to the need to increase state intervention in the activities of entrepreneurs is shown. The state support of business for the subsequent development of the economy and compliance with the social balance is also increasing. Accordingly, the social importance of entrepreneurial activity is growing. The pandemic has also intensified the digitalization of entrepreneurial activity, of transport companies, since many traditional forms of doing business are limited by the forced isolation of society. Individual means of digitalization, including the industrial Internet of Things, e-commerce, and smart contracts, have become most prevalent. Consequently, the pandemic cannot be viewed only as a negative factor, its impact on entrepreneurial activity also has a positive effect.
Keywords: Business; axiology; digitalization; means of legal regulation; pandemic; transport companies

Airport Charges Regulation: A Private Law Approach - Mei, Di (McGill University, 2022)
This thesis explores the regulation of airport charges, which is an important but marginalised topic. It particularly examines how private law instruments can play a role in the regulatory process. Airports used to be subject to traditional regulation, which operates in a command-and-control mode. As the airport industry becomes increasingly complicated, traditional regulation seems problematic. First, the method that is associated with traditional regulation to draw a line between regulated and unregulated airports has downsides. Second, the international regulatory framework on airport charges lacks binding rules. This suggests that traditional regulation is not the best niche for airport charges regulation. Third, good regulation needs independent regulatory bodies, which are hard to achieve in practice.In this context, this thesis argues that a private law approach can serve as a more flexible and effective way to regulate airport charges. There are two instruments under this overarching approach. First, contracts can be adopted to incorporate airport charges regulations. Second, robust corporate governance generates the effect of good regulation. This is an interdisciplinary work that has engaged air law, contract law, corporate law, competition law, and aviation business and management. It also employs the method of case studies. Chapter 4 examines the regulation of airport charges in the UK, Canada, and India. The three case studies demonstrate that private law instruments have been implicitly implemented to different degrees in these countries. These demonstrate the feasibility of applying private ordering in the regulatory process. I also look into the regulation of countries and regions including Australia, Ireland, the EU, and Germany throughout this thesis. This study also examines a specific sector of airport charges, namely, charges for ground-handling services. This sector possesses a unique feature in that it is between aeronautical and non-aeronautical services. A private law approach can also be adopted in the regulation of charges relating to ground-handling services. Additionally, ICAO as an important international organisation governing international air transport can also contribute to a private law approach of airport charges through its soft-law making function. This thesis aims to shed light on a private law approach, as an innovative regulatory mechanism, to airport charges. That said, regulation by this approach and traditional regulation are not contradictory but can cooperate to an extent, depending on how much power one wants to give to private ordering
Identifier: https://escholarship.mcgill.ca/concern/theses/8910k0504
Keywords: Airport; Regulation